2021
DOI: 10.1002/cli2.15
|View full text |Cite
|
Sign up to set email alerts
|

Extreme rainfall and its impacts in the Brazilian Minas Gerais state in January 2020: Can we blame climate change?

Abstract: In January 2020, an extreme precipitation event occurred over southeast Brazil, with the epicentre in Minas Gerais state. Although extreme rainfall frequently occurs in this region during the wet season, this event led to the death of 56 people, drove thousands of residents into homelessness, and incurred millions of Brazilian Reais (BRL) in financial loss through the cascading effects of flooding and landslides. The main question that arises is: To what extent can we blame climate change? With this question i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 59 publications
2
24
0
3
Order By: Relevance
“…Moreover, extreme rainfall events and prolonged droughts observed in recent years in southeastern Brazil (Dalagnol et al. 2021; Geirinhas et al. 2021) could also lead to reduced survival of pond‐breeding anurans, particularly those using ephemeral ponds and with reduced reproductive season.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, extreme rainfall events and prolonged droughts observed in recent years in southeastern Brazil (Dalagnol et al. 2021; Geirinhas et al. 2021) could also lead to reduced survival of pond‐breeding anurans, particularly those using ephemeral ponds and with reduced reproductive season.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we have shown that sex-related differences in responses to environmental cues can exacerbate phenological shifts in amphibian migrations as climate change intensifies in the region, and potentially impact the mating success of forestdependent pond-breeding species. Moreover, extreme rainfall events and prolonged droughts observed in recent years in southeastern Brazil (Dalagnol et al 2021;Geirinhas et al 2021) could also lead to reduced survival of pond-breeding anurans, particularly those using ephemeral ponds and with reduced reproductive season.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in January 2020, extreme rainfall and resulting flood and landslides in Minas Gerais state in Southeast Brazil led to the death of 56 people, and an estimated 90,000 people became temporarily homeless. Dalagnol et al (2021) estimate this event to be more than 70% more likely due to human-induced climate change.…”
Section: Science For Adaptationmentioning
confidence: 99%
“…The threshold used to define the drought event was defined as the average of the standardized seasonal precipitation of the two lowest standardized seasonal precipitation values from CHIRPS prior to 2015/2016 which were 1982/1983 and 1991/1992. This approach avoids overselection for the observed threshold and was based on the methods used by Dalagnol et al (2021) and de Abreu et al (2019). We also tested the sensibility of the RR to threshold values.…”
Section: Event Attributionmentioning
confidence: 99%